A New Dual Band Printed Metamaterial Antenna for RFID Reader Applications - Abdelhadi Ennajih; Jamal Zbitou; Mohamed Latrach; Ahmed Errkik; Rachid Mandry (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In this paper, we present a new dual band metamaterial printed antenna for radio frequency identification applications. The proposed antenna consists of two L-shaped slot in the radiating element for dual band operation and a complementary split ring resonator etched from the ground plane for size miniaturization. This antenna is designed and optimized by CST microwave studio on FR-4 substrate with thickness of 1.6 mm, dielectric constant of 4.4 and tangent loss of 0.025. A microstrip line with characteristic impedance of 50 ohms is used to feed this antenna. A prototype of the proposed antenna is fabricated to validate the simulation results. The measured and simulated results are in good agreement.